2017
DOI: 10.3892/mmr.2017.7159
|View full text |Cite
|
Sign up to set email alerts
|

microRNA-630 promotes cell proliferation and inhibits apoptosis in the HCT116 human colorectal cancer cell line

Abstract: Dysregulation of microRNAs (miRNAs) in colorectal cancer provides important opportunities for the development of future miRNA‑based therapies. The present study aimed to assess the role of miRNA‑630 (miR‑630) expression in colorectal cancer. HCT116 human colorectal cancer cells were transfected with miR‑630 inhibitor, mimic or control miRNA, and the effects of miR‑630 dysregulation on cell viability, proliferation and apoptosis were analyzed using MTT and bromodeoxyuridine assays, and an annexin V‑fluorescein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 29 publications
1
11
0
Order By: Relevance
“…Most mature miRNAs precisely regulate target genes by binding to the 3'untranslated region (UTR) of their mRNAs [7]. Compelling evidence has indicated that miRNAs play vital roles in many biological processes, including tumorigenesis, apoptosis, proliferation, and cell differentiation [8][9][10]. For example, miRNA-1273g-3p and miRNA-451a have been shown to play vital roles in the regulation of DR; thus, they may serve as new targets for DR treatment [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Most mature miRNAs precisely regulate target genes by binding to the 3'untranslated region (UTR) of their mRNAs [7]. Compelling evidence has indicated that miRNAs play vital roles in many biological processes, including tumorigenesis, apoptosis, proliferation, and cell differentiation [8][9][10]. For example, miRNA-1273g-3p and miRNA-451a have been shown to play vital roles in the regulation of DR; thus, they may serve as new targets for DR treatment [11,12].…”
Section: Introductionmentioning
confidence: 99%
“… 19 In our study, we found that: (1) miR‐630 expression in tumor tissue was higher than that in non‐tumor tissue, a possible explanation might that: miR‐630 reflected the proliferation rate of cells, and meanwhile, the proliferation rate in osteosarcoma cells was higher than that in the adjacent tissue cells. Therefore, miR‐630 expression was higher in tumor tissue than in non‐tumor tissue; (2) elevated miR‐630 was correlated with the occurrence of pathological fracture and deteriorated disease severity feature, the reason might be that: elevated miR‐630 promoted malignant osteosarcoma cell proliferation, 21 which might contribute to the osteosarcoma progression, subsequently causing bone lesion and deteriorated disease feature 6 ; (3) elevated miR‐630 expression was associated with poor neoadjuvant treatment response, the explanations could be that: miR‐630 expression might increase cisplatin resistance in osteosarcoma, 22 thus causing unfavorable treatment response; (4) miR‐630 high was associated with shorter DFS, a possible reason could be that: its association with deteriorated disease feature and unfavorable treatment response (as above mentioned) might indirectly resulted in poor DFS.…”
Section: Discussionmentioning
confidence: 99%
“…(2) elevated miR-630 was correlated with the occurrence of pathological fracture and deteriorated disease severity feature, the reason might be that: elevated miR-630 promoted malignant osteosarcoma cell proliferation, 21…”
Section: Mto1 Expression Independently Correlates With Prolonged Dfsmentioning
confidence: 99%
“…miRs have been reported to serve as oncogenes or tumor suppressors to regulate cancer cell proliferation and migration. For instance, Zhang et al (26) reported that miR-630 promotes cell proliferation and inhibits apoptosis in the HCT116 human colorectal cancer cell line. Furthermore, Liu et al (27) revealed that miR-1297 contributes to tumor growth of human breast cancer by targeting PTEN/ phosphoinositide 3-kinase/AKT signaling.…”
Section: Discussionmentioning
confidence: 99%